Anatomical Facial Characteristics of Teeth and Tooth Analysis - Sybrand Gerhard de Bruin; Sundika Ishwarkumar-Govender; Pamela Pillay (Dentistry Journal)
Background: This study aimed to document the angulation, inclination, and facial anatomical characteristics of teeth in a select South African population to determine if there are any population norms. Digital intra-oral scans were used, to analyze the morphology of teeth and measure the facial clinical crown. Methods: A quantitative observational research design with 60 3D intra-oral scans of a select South African population group was used. Morphometric analysis of 3D intra-oral scans was performed for a select South African population group, measuring the clinical crown height, width, angulation, and inclination of each tooth. Results: Significant differences in crown widths between male and female subjects were observed for several teeth in the maxillary and mandibular arches: males exhibited larger mean widths and larger crown dimensions than females. The South African Black group showed more sexual dimorphism compared to the South African Indian group. Clinical crown length and tooth angulation differed significantly between South African Indian and South African Black populations, while crown width and inclination remained consistent across these population groups and crown inclination between sex groups. Conclusions: Certain teeth exhibited notable variations between South African Indian and South African Black population groups; specifically, crown length and angulation had significant differences, whereas crown inclination and width remained consistent across these population groups.